2019
DOI: 10.1590/s1980-220x2018004103472
|View full text |Cite
|
Sign up to set email alerts
|

Nursing diagnoses for institutionalized elderly people based on Henderson’s theory

Abstract: Objective: To develop nursing diagnostic statements for institutionalized elderly people. Method: Descriptive study conducted with elderly subjects of a Long Stay Institution through the application of forms for the support of anamnesis and physical examination and a search of medical records. The diagnostic statements were developed based on the International Classification for Nursing Practice and categorized according to the Henderson’s theoretical model. Results: Participation of 203 elderly people. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 9 publications
0
3
0
5
Order By: Relevance
“…23 In a study conducted with older adults living in a nursing home, most of the participants stated that, by living in harmony with nature, they realised that death was a natural phenomenon and individuals should not try to change it. 24 Another study about nursing diagnoses of elderly people living in institutions identified the need to maintain a desirable posture to prevent the common problems they encountered, 25 including musculoskeletal pain, stiffness, unstable gait and history of falls. The fact that a systematic care regimen addressing these problems among the elderly has been overlooked may have affected the results of the study.…”
Section: Discussionmentioning
confidence: 99%
“…23 In a study conducted with older adults living in a nursing home, most of the participants stated that, by living in harmony with nature, they realised that death was a natural phenomenon and individuals should not try to change it. 24 Another study about nursing diagnoses of elderly people living in institutions identified the need to maintain a desirable posture to prevent the common problems they encountered, 25 including musculoskeletal pain, stiffness, unstable gait and history of falls. The fact that a systematic care regimen addressing these problems among the elderly has been overlooked may have affected the results of the study.…”
Section: Discussionmentioning
confidence: 99%
“…Entendem-se cuidados ao fim da vida como uma abordagem dos CP que a pessoa idosa deve receber durante os últimos dias de sua vida, a partir do instante em que fica claro que ela se encontra em estado de declínio progressivo e inexorável, aproximando-se da morte (22) . Nesse contexto, o enfermeiro assume um papel de destaque no planejamento e na implementação de ações/intervenções de enfermagem voltadas para o bem-estar físico e emocional, assim como para a independência da pessoa idosa na realização das atividades da vida diária sempre que possível, devendo, para tanto, documentar sua prática com base em um suporte teórico no Processo de Enfermagem e no uso dos Sistemas de Linguagem Padronizada (23) .…”
Section: Resultados E Refelxãounclassified
“…End-of-life care is understood as an approach to PC that older adults must receive during the last days of their life, from the moment it becomes clear that they are in a state of progressive and inexorable decline, approaching death (22) . In this context, nurses have a prominent role in planning and implementing nursing actions/interventions aimed at physical and emotional well-being as well as at the independence of older adults in carrying out activities of daily living whenever possible, and should, for both, document their practice based on theoretical support in the Nursing Process and the use of Standardized Language Systems (23) .…”
Section: Results and Reflectionmentioning
confidence: 99%